2020
DOI: 10.1111/tbj.13524
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in metabolomics of triple negative breast cancer

Abstract: Triple‐negative Breast Cancer (TNBC) is considered as the most aggressive subtype of breast cancer. Metabolic profiling has a great significance in cancer research due to profound changes in the metabolism of cancer cells. It has been used to investigate the entire set of metabolites and changes associated with it in disease conditions. These changes in the expression levels of metabolites bring functional changes associated with the pharmacological or nutritional intervention. The present minireview presents … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…These metabolites exert antineoplastic effects, including modulation of cell proliferation and epithelial-mesenchymal transition (EMT) [44]. As stated earlier, the metabolic capacity of the microbiome is suppressed in breast cancer, and the capacity to produce known antineoplastic metabolites decreases in breast cancer [29][30][31][45][46][47].…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…These metabolites exert antineoplastic effects, including modulation of cell proliferation and epithelial-mesenchymal transition (EMT) [44]. As stated earlier, the metabolic capacity of the microbiome is suppressed in breast cancer, and the capacity to produce known antineoplastic metabolites decreases in breast cancer [29][30][31][45][46][47].…”
Section: Introductionmentioning
confidence: 93%
“…Oncobiosis support of breast tumors is multifaceted. (1) Bacteria colonize the tumor tissue; (2) the immune system favors the tolerogenic state [44]; and (3) the gut microbiome's capacity to produce antitumor metabolites is suppressed [29][30][31][45][46][47].…”
Section: Introductionmentioning
confidence: 99%
“…As the gut microbiome is the biggest in the body in terms of the number of bacteria, its metabolic capacity is considerable. The biosynthetic capacity of the oncobiome is suppressed compared to the eubiome [ 126 , 127 ]. Multiple bioactive bacterial metabolites were identified that can modulate the behavior of breast cancer cells (Table 3 ).…”
Section: Interactions Between the Oncobiome Tumors And Tumor Cellsmentioning
confidence: 99%